The Quest of the Historical Jesus a critical study of its progress from Reimarus to Wrede - Schweitzer, Albert (New York The Macmillan Company, 1968)
Dr. Schweitzer evaluates accounts of Jesus' life produced in the seventeenth and nineteenth centuries.
Keywords: Christology. Jesus Christ -- Biography -- History and criticism. Jesus Christ -- Historicity. Jesus Christ. Biography. Historicity of Jesus Christ